Blending Technology and Pedagogy: Optimizing Maharah al-Qirā’ah through the Alef Education Platform - Mirdawati Razida; Nur Hasaniyah; Abdul Muntaqim Al Anshory (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
This study aims to examine Optimizing Reading Skills (maharah al qira’ah) through the Alef Education Platform utilizing the Alef Education platform at MA DDI Lil Banat Parepare. The background of this research is based on the need for innovative, interactive, and technology-based learning media to effectively enhance students interest and ability in reading Arabic texts. This study employs a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation. The results show that the use of the Alef Education platform has a positive impact on the teaching of maharah al qira’ah, particularly in increasing learning motivation, text comprehension, and active student participation in the learning process. Although there are some technical challenges, such as limited internet access and insufficient initial training for teachers, the platform generally serves as an effective alternative learning medium in the madrasah environment. This study recommends the continued use of Alef Education with proper teacher training and improved technological infrastructure support in madrasah. The contribution of this study lies in providing empirical evidence on the effectiveness of using Alef Education in improving Arabic reading skills in madrasahs, as well as offering strategic recommendations for the sustainable utilization of this platform with teacher training support and the enhancement of technological facilities.